2002
DOI: 10.1002/cncr.10494
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of [18F]fluorodeoxyglucose positron emission tomography with conventional assessment by computed tomography scans and serum tumor markers for the evaluation of residual masses in patients with nonseminomatous germ cell carcinoma

Abstract: BACKGROUNDTo assess the ability of [18F]fluorodeoxyglucose (F‐18 FDG) positron emission tomography (PET) to predict the viability of residual masses after chemotherapy in patients with metastatic nonseminomatous germ cell tumors (GCT), PET results were compared in a blinded analysis with computed tomography (CT) scans and serum tumor marker changes (TUM) as established methods of assessment.METHODSIndependent reviewers who were blinded to each other's results evaluated the PET results and corresponding CT scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(24 citation statements)
references
References 36 publications
0
21
0
3
Order By: Relevance
“…FDG-PET results were compared in a blinded analysis with CT scans and serum tumor marker changes as established methods of assessment in 85 residual lesions from 45 patients with nonseminomatous disease enrolled in a prospective study [34]. PET assessment demonstrated positive and negative predictive values of 91% and 62%, respectively, in differentiating tumor from non tumor lesions.…”
Section: Nonseminomamentioning
confidence: 99%
“…FDG-PET results were compared in a blinded analysis with CT scans and serum tumor marker changes as established methods of assessment in 85 residual lesions from 45 patients with nonseminomatous disease enrolled in a prospective study [34]. PET assessment demonstrated positive and negative predictive values of 91% and 62%, respectively, in differentiating tumor from non tumor lesions.…”
Section: Nonseminomamentioning
confidence: 99%
“…Moreover, the value of PET imaging was investigated comparing it to an established prognostic model as well as to conventional means of response assessment such as CT scans/MRI and the changes of TUM levels. Studies in different tumour types have demonstrated the ability of PET to clinically document tumour response to chemotherapy as well as its diagnostic value in the staging of cancer (Huovinen et al, 1993;Findlay et al, 1996;Flamen et al, 1999;Kollmannsberger et al, 2002). Wahl et al (1993) were among the first who reported that PET may have a substantial role as an early non-invasive method for the assessment of the efficacy of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Standardized uptake values (SUV), a quantitative measure of tumour uptake of the tracer, adjusted for injected dose and body weight, were calculated, if an increased uptake was observed in the tumour area (Leskinen et al, 1991;Strauss and Conti, 1991). Patients with a SUV of 52 were considered positive (Kollmannsberger et al, 2002).…”
Section: Pet Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, fluorodeoxyglucose-positron emission tomography (FDG-PET) has been widely used for evaluating the response of gonadal GCT to chemotherapy in the management of the tumor including gonadal GCT [5]. Here, we report a case of mediastinal nonseminomatous yolk sac tumor showing a decreasing FDG uptake postchemotherapy, with no viable tumor cells histopathologically upon resection of the surgical specimen.…”
Section: Introductionmentioning
confidence: 95%